2010 Symposium on VLSI Technology 2010
DOI: 10.1109/vlsit.2010.5556185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prospect of local variability of drain current in scaled MOSFETs by a new decomposition method

Abstract: Causes of drain current local variability are analyzed by decomposing into current variability components. Besides V TH and G m components, it is newly found that effects of "current onset" variability caused by channel potential fluctuations largely contribute to the current variability and that G m component is relatively small in the saturation region. It is shown that both V TH and current onset components decreases with reducing channel dopants, indicating that intrinsic channel is very effective to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 1 publication
0
40
0
Order By: Relevance
“…9 Experiments without source/drain commutation, done on very large ensembles of specially designed transistor arrays with circuits that allow individual transistors to be accessed are also possible. 10 Special care must be taken to minimize systematic variations (i.e., mature technology and a special layout are used) in such studies. 11 Regardless of the measurement approach, experimental observations refl ect the simultaneous impact of all sources of statistical variability.…”
Section: A Note On Methodologymentioning
confidence: 99%
“…9 Experiments without source/drain commutation, done on very large ensembles of specially designed transistor arrays with circuits that allow individual transistors to be accessed are also possible. 10 Special care must be taken to minimize systematic variations (i.e., mature technology and a special layout are used) in such studies. 11 Regardless of the measurement approach, experimental observations refl ect the simultaneous impact of all sources of statistical variability.…”
Section: A Note On Methodologymentioning
confidence: 99%
“…COV is defined by the difference between extrapolated Vth (Vthex) and subthreshold constant current Vth (Vthc) (COV = Vthex -Vthc) [7,8]. COV variability is compared in Fig.…”
Section: A Dibl and Cov Variabilitymentioning
confidence: 99%
“…It is also found that the variability of "current-onset voltage (COV)" [7], which affects drain current variability, is caused by channel potential fluctuations due to RDF [8]. On the other hand, random telegraph noise (RTN) is another issue of the fluctuation of transistor characteristics [9], and the suppression of the RTN effect is essential for future scaled MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…However, I on variability (ΔI on ) has never been investigated for the FinFETs even though it directly determines the circuit performance. In addition to the ΔV t as the dominant source of ΔI on , significance of G m variation (ΔG m ) increases for the FinFET because the recent work on scaled bulk planar MOSFETs reveals that ΔG m is not suppressed by the RDF reduction [3]. The fluctuation of R para (ΔR para ) in the FinFET is a significant I on variation source too [4].…”
Section: Introductionmentioning
confidence: 99%